Positive Darwinian selection after gene duplication in primate ribonuclease genes - Zhang, Jianzhi (The National Academy of Sciences, 1998)
Evolutionary mechanisms of origins of new gene function have been a subject of long-standing debate. Here we report a convincing case in which positive Darwinian selection operated at the molecular level during the evolution of novel function by gene duplication. The genes for eosinophil cationic protein (ECP) and eosinophil-derived neurotoxin (EDN) in primates belong to the ribonuclease gene family, and the ECP gene, whose product has an anti-pathogen function not displayed by EDN, was generated by duplication of the EDN gene about 31 million years ago. Using inferred nucleotide sequences of ancestral organisms, we showed that the rate of nonsynonymous nucleotide substitution was significantly higher than that of synonymous substitution for the ECP gene. This strongly suggests that positive Darwinian selection operated in the early stage of evolution of the ECP gene. It was also found that the number of arginine residues increased substantially in a short period of evolutionary time after gene duplication, and these amino acid changes probably produced the novel anti-pathogen function of ECP.